Experimenting with ecosystem interaction networks in search of threshold potentials in real‐world marine ecosystems. Issue 6 (1st June 2014) - Thrush, Simon F.; Hewitt, Judi E.; Parkes, Samantha; Lohrer, Andrew M.; Pilditch, Conrad; Woodin, Sarah A.; Wethey, David S.; Chiantore, Mariachiara; Asnaghi, Valentina; De Juan, Silvia; Kraan, Casper; Rodil, Ivan; et al.
Abstract : Thresholds profoundly affect our understanding and management of ecosystem dynamics, but we have yet to develop practical techniques to assess the risk that thresholds will be crossed. Combining ecological knowledge of critical system interdependencies with a large‐scale experiment, we tested for breaks in the ecosystem interaction network to identify threshold potential in real‐world ecosystem dynamics. Our experiment with the bivalves Macomona liliana and Austrovenus stutchburyi on marine sandflats in New Zealand demonstrated that reductions in incident sunlight changed the interaction network between sediment biogeochemical fluxes, productivity, and macrofauna. By demonstrating loss of positive feedbacks and changes in the architecture of the network, we provide mechanistic evidence that stressors lead to break points in dynamics, which theory predicts predispose a system to a critical transition.